Women and Pleasure in Guillaume Apollinaire’s Calligram Collection Poèmes à Lou - Eva Agustin; Wening Udasmoro (k@ta: A Biannual Publication on the Study of Languange and Literature, 2018)
This article attempts to examine the connections between poetry and the constructions of women and pleasure emphasized by the author. The works examined are those of Gullaume Apollinaire, a famed French poet whose calligramatic poetry collections specifically positioned women as objects of pleasure. Most interestingly, in Apollinaire's poetry the depiction of women as objects of pleasure through connotative symbols that can only be given significance by decoding the highly cultural meanings they contain. The theory of the male gaze is used here to examine how visual pleasure has been operated by the poet. Meanwhile, semiotics has been used to decode the calligrammatic aspects of Apollinaire's poems. This research finds that symbols of exoticism, reproduction, and fantastic pleasures are utilized by Apollinaire in his poetry to emphasize his dominance of women by positioning them as objects of pleasure.